Population Pharmacokinetic Modeling and Exposure–Response Assessment for the Antibody‐Drug Conjugate Brentuximab Vedotin in Hodgkin's Lymphoma in the Phase III ECHELON‐1 Study. Issue 6 (9th July 2019) - Suri, Ajit; Mould, Diane R.; Song, Gregory; Collins, Graham P.; Endres, Christopher J.; Gomez‐Navarro, Jesús; Venkatakrishnan, Karthik
Abstract : The efficacy of the CD30‐directed antibody‐drug conjugate (ADC) brentuximab vedotin was established in combination with chemotherapy as frontline treatment for advanced classical Hodgkin's lymphoma in the randomized phase III ECHELON‐1 study. Population pharmacokinetic (PK) and exposure–response models were developed to quantify sources of PK variability and relationships between exposure and safety/efficacy end points in ECHELON‐1. The influence of patient‐specific factors on the PK of the ADC and the microtubule‐disrupting payload monomethyl auristatin E (MMAE) was investigated; none of the significant covariates had a clinically relevant impact. Exposure–response analyses evaluated relationships between time‐averaged area under the curve (AUC; ADC, MMAE) and efficacy end points (ADC) or safety parameters (ADC, MMAE). Exposure–efficacy analyses supported consistent treatment benefit with brentuximab vedotin across observed exposure ranges. Exposure‐safety analyses supported the recommended brentuximab vedotin starting dose (1.2 mg/kg every 2 weeks), and effective management of peripheral neuropathy and neutropenia with dose modification/reduction and febrile neutropenia with granulocyte colony‐stimulating factor primary prophylaxis.